Strain-specific programming of prenatal ethanol exposure across generations. - Popoola, Daniel O; Nizhnikov, Michael E; Cameron, Nicole M (Alcohol (Fayetteville, N.Y.), 2017)
Behavioral consequences of prenatal alcohol exposure (PAE) can be transmitted from in utero-exposed F1 generation to their F2 offspring. This type of transmission is modulated by genetic and epigenetic mechanisms. This study investigated the intergenerational consequences of prenatal exposure to a low ethanol dose (1 g/kg) during gestational days 17-20, on ethanol-induced hypnosis in adolescent male F1 and F2 generations, in two strains of rats. Adolescent Long-Evans and Sprague-Dawley male rats were tested for sensitivity to ethanol-induced hypnosis at a 3.5-g/kg or 4.5-g/kg ethanol dose using the loss of righting reflex (LORR) paradigm. We hypothesized that PAE would attenuate sensitivity to ethanol-induced hypnosis in the ethanol-exposed animals in these two strains and in both generations. Interestingly, we only found this effect in Sprague-Dawley rats. Lastly, we investigated PAE related changes in expression of GABAA receptor alpha1, alpha4, and delta subunits in the cerebral cortex of the PAE sensitive Sprague-Dawley strain. We hypothesized a reduction in the cerebral cortex GABAA receptor subunits' expression in the F1 and F2 PAE groups compared to control animals. GABAA receptor alpha1, alpha4, and delta subunits protein expressions were quantified in the cerebral cortex of F1 and F2 male adolescents by western blotting. PAE did not alter cerebral cortical GABAA receptor subunit expressions in the F1 generation, but it decreased GABAA receptor alpha4 and delta subunits' expressions in the F2 generation, and had a tendency to decrease alpha1 subunit expression. We also found correlations between some of the subunits in both generations. These strain-dependent vulnerabilities to ethanol sensitivity, and intergenerational PAE-mediated changes in sensitivity to alcohol indicate that genetic and epigenetic factors interact to determine the outcomes of PAE animals and their offspring. Copyright © 2017 Elsevier Inc. All rights reserved.
9 citations (Crossref) [2023-10-31] Place: United States Popoola, Daniel O. Psychology Department, Center for Developmental and Behavioral Neuroscience, Developmental Exposure Alcohol Research Center, Binghamton University- SUNY, 4400 Vestal Parkway East, Binghamton, NY 13902, USA. Nizhnikov, Michael E. Southern Connecticut State University, 501 Crescent Street, New Haven, CT, 06515-1355, USA. Cameron, Nicole M. Psychology Department, Center for Developmental and Behavioral Neuroscience, Developmental Exposure Alcohol Research Center, Binghamton University- SUNY, 4400 Vestal Parkway East, Binghamton, NY 13902, USA. Electronic address: ncameron@binghamton.edu.
Keywords: *Alcohol Drinking/ae [Adverse Effects]; *Behavior; Animal/de [Drug Effects]; *Cerebral Cortex/de [Drug Effects]; *Ethanol/to [Toxicity]; *Prenatal Exposure Delayed Effects; *Receptors; GABA-A/de [Drug Effects]; 4 aminobutyric acid A receptor; 4 aminobutyric acid A receptor alpha1; 4 aminobutyric acid A receptor alpha4; Age Factors; Alcohol Drinking; Alcohol Drinking/ge [Genetics]; Alcohol Drinking/me [Metabolism]; Alcohol Drinking/px [Psychology]; Animals; Article; Behavior; Animal; Blood Alcohol Content; Cerebral Cortex; Cerebral Cortex/me [Metabolism]; Cerebral Cortex/pa [Pathology]; Dose-Response Relationship; Drug; Epigenesis; Genetic; Epigenesis; Genetic/de [Drug Effects]; Ethanol; Ethanol/bl [Blood]; Female; Gestational Age; Long Evans rat; Male; Maternal Exposure; Pregnancy; Prenatal Exposure Delayed Effects; Rats; Long-Evans; Rats; Sprague-Dawley; Reaction Time; Receptors; GABA-A; Receptors; GABA-A/ge [Genetics]; Receptors; GABA-A/me [Metabolism]; Reflex; Righting; Reflex; Righting/de [Drug Effects]; Species Specificity; Sprague Dawley rat; Time Factors; Western blotting; adolescent; adult; age; alcohol; alcohol blood level; alcohol consumption; animal; animal behavior; animal experiment; animal model; animal tissue; blood; brain cortex; comparative study; controlled study; correlational study; dept.psy; dose response; drinking behavior; drug effects; epigenetics; female; genetic epigenesis; genetics; gestation period; gestational age; hemoglobin delta chain; heredity; hypnosis; male; maternal exposure; metabolism; nonhuman; outcome assessment; pathology; peer-reviewed; pregnancy; prenatal exposure; progeny; protein expression; psychology; rat